1994
DOI: 10.1111/j.1439-037x.1994.tb00173.x
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Sugarcane (Saccharum officinarum L.) Under Surface Drip, Sub Surface Drip (Biwall) and Furrow Methods of Irrigation

Abstract: Field experiments were conducted at the Sugarcane Breeding Institute, Coimbatore, India during 1989–93 to study the productivity and water use efficiency of sugarcane under different methods of irrigation. The results showed that there could be a 44 % saving in water with higher water use efficiency in drip irrigation compared to conventional furrow irrigation. Among drip irrigation systems in the plant crop, sub surface drip (Biwall) at 40/140 cm spacing recorded a significantly higher number of millable cane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
1

Year Published

1997
1997
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 0 publications
1
4
0
1
Order By: Relevance
“…Similar trend was noticed in number of millable canes and commercial cane sugar. Ramesh et al (1994) also reported that drip irrigation gave higher cane yield than furrow irrigation based on IW: CPE ratio.…”
Section: Performance Of Drip and Surface Irrigationmentioning
confidence: 93%
“…Similar trend was noticed in number of millable canes and commercial cane sugar. Ramesh et al (1994) also reported that drip irrigation gave higher cane yield than furrow irrigation based on IW: CPE ratio.…”
Section: Performance Of Drip and Surface Irrigationmentioning
confidence: 93%
“…A resposta de produtividade da cana-de-açúcar irrigada depende de um conjunto de fatores, dentre eles: da quantidade de água e de fertilizantes aplicados (Thorburn et al, 2003;Dantas Neto et al, 2006), do manejo de irrigação (Ramesh et al, 1994), da cultivar, idade de corte e do tipo de solo e do clima (Ramesh & Mahadevaswamy, 2000;Smit & Singels, 2006). Portanto, o presente trabalho teve como objetivo estudar o efeito da tecnologia de irrigação por gotejamento, em diferentes cultivares de cana-de-açúcar, em dois ciclos de produção (cana--planta e cana-soca).…”
Section: Introductionunclassified
“…With good management practices, deficit irrigation can result in substantial water savings with little impact on the quality and quantity of the yield in cotton (Kirda 2002) and soya bean (Sincik et al 2008). A number of previous studies reported the advantage of drip irrigation methods in terms of high WUE and yield for different crops including cotton (Mateos et al 1991, Weerathaworn et al 1992, Abu-Awwad 1994, Ramesh et al 1994, Dagdelen et al 2006, Ibragimov et al 2007, El-Hendawy et al 2008.…”
Section: Introductionmentioning
confidence: 99%